Von Economo Neurons in the Human Medial Frontopolar Cortex - Carlos Arturo González-Acosta; Martha Isabel Escobar; Manuel Fernando Casanova; Hernán J. Pimienta; Efraín Buriticá (Frontiers Media S.A., 2018)
The von Economo neurons (VEN) are characterized by a large soma, spindle-like soma, with little dendritic arborization at both, the basal and apical poles. In humans, VENs have been described in the entorhinal cortex, the hippocampal formation, the anterior cingulate cortex, the rostral portion of the insula and the dorsomedial Brodmann's area 9 (BA9). These cortical regions have been associated with cognitive functions such as social interactions, intuition and emotional processing. Previous studies that searched for the presence of these cells in the lateral frontal poles yielded negative results. The presence of VENs in other cortical areas on the medial surface of the human prefrontal cortex which share both a common functional network and similar laminar organization, led us to examine its presence in the medial portion of the frontal pole. In the present study, we used tissue samples from five postmortem subjects taken from the polar portion of BA10, on the medial surface of both hemispheres. We found VENs in the human medial BA10, although they are very scarce and dispersed. We also observed crests and walls of the gyrus to quantitatively assess: (A) interhemispheric asymmetries, (B) the VENs/pyramidal ratio, (C) the area of the soma of VENs and (D) the difference in soma area between VENs and pyramidal and fusiform cells. We found that VENs are at least seven times more abundant on the right hemisphere and at least 2.5 times more abundant in the crest than in the walls of the gyrus. The soma size of VENs in the medial frontopolar cortex is larger than that of pyramidal and fusiform cells of layer VI, and their size is larger in the walls than in the crests. Our finding might be a contribution to the understanding of the role of these neurons in the functional networks in which all the areas in which they have been found are linked. However, the particularities of VENs in the frontal pole, as their size and quantity, may also lead us to interpret the findings in the light of other positions such as van Essen's theory of tension-based brain morphogenesis.